Recruitment to a prospective breast conservation trial: why are so few patients randomised?. Issue 6743 (14th July 1990) - Jack, W J; Chetty, U; Rodger, A
Abstract : OBJECTIVE–To investigate the rate of recruitment to early breast cancer trials and elucidate the reasons for ineligibility and refusal to participate among patients otherwise suitable for these trials. DESIGN–Prospective study of one year's cohort of patients referred to a breast unit with special reference to the subgroup suitable for conservation management and to the proportion eligible for and (after informed consent) ultimately randomised within the Scottish early breast cancer trials. SETTING–The breast unit, Longmore Hospital, Edinburgh, during 1988. PATIENTS–All 3054 patients referred to the breast unit during the year. 324 Found to have invasive breast cancer and 147 initially thought suitable for conservation management. RESULTS–63 Patients were treated by mastectomy, 19 of whom requested mastectomy rather than conservation management. 84 Patients were excluded from trials, and of the 63 eligible patients, 40 gave informed consent. Most of the 23 patients who refused the trials requested a specific adjuvant treatment after discussion of their management and the trials. CONCLUSIONS–Recruitment to prospective trials in which informed consent is required before randomisation may be slower than predicted because of a high proportion of exclusions and also refusal by patients. Trials may therefore take longer to complete and give distorted results by virtue of the unpredictable nature of the selection of patients.